Persistence of Cholinesterase Inhibitor Treatment in Dementia: Insights from a Naturalistic Study - Javier Olazarán; Eloísa Navarro; José Manuel Rojo (Dementia and Geriatric Cognitive Disorders Extra, 2013)
Background: Cholinesterase inhibitors (ChEI) are widely used in dementia, but there is a lack of practice guidelines in case of intolerance or absence of perceived effect. Methods: Two hundred and forty patients (mean age 77 years, SD 6.3, 66% female) with Alzheimer's disease or Lewy body dementia were prescribed a ChEI and evaluated annually under conditions of standard practice. Of these, 152 patients maintained, 36 switched, and 52 abandoned ChEI treatment. Results: Less behavioural disturbance and less cognitive deterioration were observed, respectively, at the 3- and 4-year follow-up assessments in the patients who maintained the first prescribed ChEI (p Conclusions: Maintenance of the first prescribed ChEI was supported when some benefit was perceived by the patient or caregiver, even in cases of nonserious adverse events.